Growth and survival performance of bileh fish (Rasbora sp.) added tarum leaf flour (Indigofera zollingeriana) - Vera Gustria; Fazril Saputra; Yusran Ibrahim; Fitria Rahmayanti; Irna Martisa; Maulida Kisma; Ariansyah Ariansyah (Program Studi Akuakultur, Fakultas Pertanian, Universitas Almuslim, 2024)
The catch of bileh fish (Rasbora sp.) has been caught from nature. Continuous fishing will lead to extinction in its habitat. Efforts made to anticipate this are carried out in the cultivation process. In fish farming, feed has a role as a source of nutrition for the growth process and survival of fish to be cultivated. Feed needs to support growth must have the right or appropriate nutritional content. The purpose of this study was to see the effect of adding tarum leaf meal (Indigofera zollingeriana) added to the feed by looking at the growth rate and survival of bileh fish (Rasbora sp.). This study used a complete randomized design (CRD), which consisted of four treatments then each treatment was repeated three times. The treatment.ie P0: control, P1: 10%, P2: 20%, and P3: 30% additional needle leaf flour. The test parameters observed were weight gain, length gain, feed conversion ratio, specific growth rate and survival. The results ANOVA test showed that the feed added with tarum leaf flour had a significant effect (P<0,05) on length increase and specific growth rate, and there was no significant effect (P>0,05) on weight gain, feed conversion ratio, and survival.